Reproductive Determinants of Breast Cancer in Women in Indonesia - Sukma, Sukmayenti; Effendi, Nursyirwan; Harahap, Wisma Arif; Dasman, Hardisman (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The number of breast cancer cases has increased every year both in the world and in Indonesia, so that breast cancer has become a major health problem both in the world and in Indonesia. The specific cause of breast cancer is still not known with certainty, but many factors are thought to influence the development of breast cancer which are called risk factors. In women, reproductive factors are thought to influence the incidence of breast cancer. AIM: This study aims to determine the determinants of breast cancer in women in terms of reproductive factors. METHOD: This research is a quantitative research with a case control study design through a retrospective approach using a questionnaire instrument. The sample size obtained was 100 women with breast cancer (case sample) and 100 women without breast cancer (control sample) (1:1), so the total sample was 200 people. Data were analyzed bivariately using chi-square test, and multivariate using logistic regression test. RESULTS: From this study it is known that the reproductive factor associated with the incidence of breast cancer in women is the age of menarche with a value of p = 0.034 OR = 1.83 CI = 1.045-3.207, the age of giving birth to the first child with a value of p = 0.000 OR = 6.39 CI = 2,521-16,243, parity with p-value = 0.022 OR = 2.14 CI = 1.107-4.152, and history of breastfeeding with p-value = 0.000 OR = 4.16 CI = 1.967-8.830. Meanwhile, the age of menopause had no relationship with the incidence of breast cancer where the p-value was 0.384. Based on the results of multivariate analysis, it was found that the most dominant factor was the age at birth of the first child with a value of p = 0.002, Exp (B) = 5, 11 and CI = 1, 85-14, 10. CONCLUSION: The results of this study indicate that reproductive factors in women (age of menarche, age at first birth, parity, and history of breastfeeding) are risk factors for breast cancer. Based on the results of this study, women must get married immediately if they have entered the ideal age for marriage and do not delay having children so that they can immediately carry out the breastfeeding process to minimize risk factors to avoid breast cancer.